A dominant gene for developmental dyslexia on chromosome 3. Issue 10 (1st October 2001) - Nopola-Hemmi, Jaana; Myllyluoma, Birgitta; Haltia, Tuomas; Taipale, Mikko; Ollikainen, Vesa; Ahonen, Timo; Voutilainen, Arja; Kere, Juha; Widén, Elisabeth
Abstract : Developmental dyslexia is a neurofunctional disorder characterised by an unexpected difficulty in learning to read and write despite adequate intelligence, motivation, and education. Previous studies have suggested mostly quantitative susceptibility loci for dyslexia on chromosomes 1, 2, 6, and 15, but no genes have been identified yet. We studied a large pedigree, ascertained from 140 families considered, segregating pronounced dyslexia in an autosomal dominant fashion. Affected status and the subtype of dyslexia were determined by neuropsychological tests. A genome scan with 320 markers showed a novel dominant locus linked to dyslexia in the pericentromeric region of chromosome 3 with a multipoint lod score of 3.84. Nineteen out of 21 affected pedigree members shared this region identical by descent (corrected p<0.001). Previously implicated genomic regions showed no evidence for linkage. Sequencing of two positional candidate genes, 5HT1F and DRD3, did not support their role in dyslexia. The new locus on chromosome 3 is associated with deficits in all three essential components involved in the reading process, namely phonological awareness, rapid naming, and verbal short term memory.